Reconstruction of combined thumb amputation at the metacarpal base level and index amputation at the metacarpal level with pollicization and bilateral double toe composite transfer. Issue 8 (August 2017) - Chi, Zhenglin; Song, Da Jiang; Tian, Lin; Hu, Fu Hua; Shen, Xiao Fang; Chim, Harvey
Summary: Background: This study aimed to describe the technique and report our experience with the reconstruction of combined proximal thumb amputations at the metacarpal base level and index finger amputation at the metacarpal level with pollicization and bilateral double toe composite transfer. Methods: The technique consists of pollicization of the remnant index ray. Then a contralateral composite medial great toe pulp and vascularized second toe proximal interphalangeal joint flap are harvested to reconstruct the metacarpophalangeal joint of the thumb. Subsequently, an ipsilateral composite great toe wrap-around and second toe proximal interphalangeal joint flap are harvested to reconstruct the thumb interphalangeal joint and the distal thumb. A neurotized superthin anterolateral thigh flap is used to reconstruct the ipsilateral toe defect, while the bone defects of the bilateral second toes are reconstructed with corticocancellous iliac crest bone grafts. Between 2010 and 2014, eight patients underwent reconstruction. Four patients could be recalled for follow-up, with a mean duration of 22 months. Results: All flaps survived. The contour and length of the reconstructed thumbs was similar to the contralateral one. The mean Michigan hand outcomes questionnaire score was 80.5. The mean disabilities of the arm, shoulder and hand score was 7.5. The mean foot and ankle disability index score was 94.2. Conclusions: Reconstruction of thumb amputations at the metacarpal base level with pollicization and double toe composite transfer results in excellent contour and functional outcome, with a natural-appearing thumb. In addition, all toes are preserved. Level of evidence: Therapeutic, Level IV